Feminist International Assistance Policy Kanada: Studi Kasus Bantuan CFLI untuk Jakarta Feminist 2017–2021 - Al Anbiya, Sekarbumi Drajad; Maliki, Musa; Akbar Setiawan, M. Chairil (Andalas Institute of International Studies UNAND, 2022)
This article aims to analyze the assistance provided by the Canada Fund for Local Initiatives to the Jakarta Feminist in the 2017-2021 period as one of the proofs that Canada's Feminist International Assistance Policy has so far been running smoothly. In addition, this article also aims to correct the misunderstandings of foreign policy observers regarding FIAP as a feminist foreign policy. FIAP has so far only used elements of Liberal Feminism as a lens of observation to focus on their foreign aid agenda to achieve a safe, inclusive, and prosperous world development. Therefore, this article argues that FIAP does contain elements of Feminism but focuses more on assisting non-profit organizations in developing countries, one of which is Indonesia. By using a descriptive qualitative research method that processes primary and secondary data from personal interviews and literature review, this article finds that CFLI, under the auspices of FIAP, has been successful in assisting the Jakarta Feminist in 2017-2021 and has also managed to reveal that FIAP is not a feminist foreign policy. FIAP oversees several foreign aid programs initiated by Canada for developing countries, one of which is CFLI.